Urgensi Etika Profesi dalam Digital Marketing Produk Halal di Kalangan Milenial - Ahmad Kamalul Fikri; Isti Mufidah (SIL'AH: Jurnal Ekonomi Syariah, 2025)
This research aims to identify the implementation of professional ethics in digital marketing of halal products among millennials with a focus on ethical issues related to the Islamic economy. The method used is descriptive qualitative with data collection techniques through in-depth interviews, participatory observation, and documentation studies on millennial digital marketers of halal products. The collected data were analyzed using a thematic analysis method with an inductive approach. The results showed that millennial business actors consistently applied the principles of honesty, fairness, and transparency in the digital marketing of halal products and avoided practices that could cause uncertainty and fraud. Educational efforts, training, and transparent communication are key to strengthening the application of professional ethics and building customer loyalty. This study contributes to the importance of applying professional ethics in digital marketing of halal products among millennials, not only to meet sharia requirements, but also as an effective business strategy to build business sustainability